2022
DOI: 10.3390/fermentation8080374
|View full text |Cite
|
Sign up to set email alerts
|

Strategy Development for Microalgae Spirulina platensis Biomass Cultivation in a Bubble Photobioreactor to Promote High Carbohydrate Content

Abstract: As a counter to climate change, energy crises, and global warming, microalgal biomass has gained a lot of interest as a sustainable and environmentally favorable biofuel feedstock. Microalgal carbohydrate is considered one of the promising feedstocks for biofuel produced via the bioconversion route under a biorefinery system. However, the present culture technique, which uses a commercial medium, has poor biomass and carbohydrate productivity, creating a bottleneck for long-term microalgal-carbohydrate-based b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…In corroboration, Cuellar-Bermudez et al [35], found that when Arthrospira is grown under nitrogen-poor conditions, it reduces the protein content and accumulates carbohydrates (up to 57-77% of dry weight), generally glycogen [37]. Similar results have been shared by Saxena et al [38] in A. platensis. Acclimatization to N starvation is probably the best example of complexity in molecular responses.…”
Section: Discussionsupporting
confidence: 59%
“…In corroboration, Cuellar-Bermudez et al [35], found that when Arthrospira is grown under nitrogen-poor conditions, it reduces the protein content and accumulates carbohydrates (up to 57-77% of dry weight), generally glycogen [37]. Similar results have been shared by Saxena et al [38] in A. platensis. Acclimatization to N starvation is probably the best example of complexity in molecular responses.…”
Section: Discussionsupporting
confidence: 59%
“…The chemical composition of Spirulina has been proven to depend on the geographic region, year, season, climatic conditions, environmental factors, cultivation, and processing methods, as well as the strain used in the bioreactor. The significant variability in research results regarding its chemical composition is also due to the diverse cultivation conditions (acidity, temperature, exposure to light, and drying methods) [43][44][45][46]. The chemical composition of 15 strains of Spirulina, cultivated in controlled environments across various countries (Ethiopia, Kenya, Chad, Mexico, USA, India, Peru, Spain), was investigated by Muhling et al [43].…”
Section: Resultsmentioning
confidence: 99%
“…All the analyses were conducted with a p-value < 0.05. The software utilized was developed by Doctor Emilio Olivares-Sáenz from the Agronomy School at the Autonomous University of Nuevo Leon (UANL), San Nicolás de lo Garza, México [21].…”
Section: Discussionmentioning
confidence: 99%
“…The flask was shaken manually four times a day. This inoculum and conditions were used for all the experiments [20,21].…”
Section: Arthrospira Platensis Inoculum Culture Conditionsmentioning
confidence: 99%